How elevated nitrogen load affects bacterial community structure and nitrogen cycling services in coastal water - Lo, Linus Shing Him; Xu, Zhimeng; Lee, Sangwook Scott; Lau, Wing Keung; Qiu, Jian-Wen; Liu, Hongbin; Qian, Pei-Yuan; Cheng, Jinping (Frontiers in Microbiology, 2022)
Nutrient pollution in the coastal environment has been accelerated by progressively intensifying aquaculture activities. Excessive nutrients can lead to coastal eutrophication with serious economic and ecological consequences. In this study, we studied coastal planktonic microbial community over a year to understand the aquaculture impact on coastal water quality and function. We observed increased total inorganic nitrogen concentrations in active fish farms to favor the diverse Alpha- and Gammaproteobacteria. Bacterial community alpha diversity in fish farms was positively correlated with total inorganic nitrogen, with active farming being an important co-influencing factor of beta diversity and structural composition alongside regional spatial variation. By analyzing the nitrogen cycle-related functional compositions and pathways using PICRUSt2 prediction on inferred genomes, we identified the contribution of over 600 bacterial species to four major pathways. Enhanced nitrogen load in active fish farms was positively correlated with elevated dissimilatory nitrate reduction and denitrification pathway abundances. Fallowed fish farms were characterized by a predicted high abundance of nirA and narB genes contributing to assimilatory nitrate reduction pathway due to the prevalence of Cyanobacteria. Overall, these results suggested active operation and short hiatus in coastal aquaculture practices could rapidly impact planktonic bacterial communities and further influence nitrogen cycling and associated processes. These findings will improve the understanding of the responses and interactions between microbiome and aquaculture activities. In a world of increasing aquaculture demands, this work has important implications for sustainable water resource management and development.